A measuring method of gas leakage along the contact interface of the stripped rubber seals. (February 2015) - Ke, YuChao; Yao, XueFeng; Yang, Heng; He, Qiang
Highlights: The measurement principle of the gas leakage along contact interface is proposed. The measurement device is built and the system errors are analyzed. The leakage along contact interface is measured by the measurement device. The gas leakage is described by Darcy–Forchheimer equation. Abstract: A measurement method of the gas leakage is introduced to characterize the gas flow along the contact interface between the woven fabric rubber seals and the metal. The measurement principle of the gas leakage along the contact interface is proposed and the measurement equipment is developed. The corresponding system errors of the measurement device are analyzed. The gas leakage along the contact interface is measured, which indicates that the leakage performance along the contact interface between the rubber seals and the metal is similar to the permeability in porous media based on Darcy–Forchheimer equation.